Analysis of The Process of Implementing Employee Recruitment, Selection, and Job Placement Case Study at PT. Samudra Abadi Nusantara Gemilang Malang City - Alwi Haidar; Hakim, Abdurrahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to describe comprehensively the recruitment, selection, and job placement processes at PT Samudra Abadi Nusantara Gemilang (SANG) and identify and analyze the challenges encountered in these processes. Design/Methodology/Approach – This study employs a descriptive research method with a qualitative approach. Data were obtained from informants, events, and documents related to the recruitment, selection, and placement processes at PT SANG. The study analyzes operational challenges to evaluate the effectiveness of workforce outsourcing services. Findings – The results indicate several challenges in the recruitment, selection, and placement stages. During recruitment, PT SANG faces difficulties in finding candidates quickly due to urgent client staffing demands. In the selection phase, challenges include candidate absences during interviews and difficulties in matching candidate skills with job requirements. In the placement phase, issues involve limited facilities, insufficient operational support, and delays in job commencement caused by client-related factors. These findings highlight the need for improved coordination and resource management to enhance process efficiency and service effectiveness. Originality/Value This study offers an in-depth qualitative analysis of practical obstacles across all staffing stages within an outsourcing firm, a topic rarely explored in detail. The findings provide context-specific insights that highlight systemic coordination and resource issues, offering valuable guidance for improving staffing efficiency and service effectiveness.